Protest voting in 2024 single candidate local elections: Empty box votes, abstention, and electoral legitimacy - Imam Syahid; Muhammad Reza Fahlevy; Widya Astuti; Merina Afrilia (JURNAL ILMU SOSIAL, 2026)
The increasing number of single candidate regional head elections in Indonesia's 2024 local elections raises questions about how electoral legitimacy should be understood under conditions of restricted competition. Although such contests are formally decided through the victory of the sole candidate pair or the empty box, this study shows that their political meaning cannot be explained through the result alone. This study uses descriptive qualitative analysis of secondary electoral data from 37 regions that held single candidate local elections in 2024, supported by official election documents, regulations, and academic sources. The analysis was carried out through classification, comparison, and interpretative reading, drawing on the concept of protest voting and Beetham's theoretical framework of electoral legitimacy. The results show four broad patterns of voter response: dominant single candidate victories, significant empty box support, high abstention, and empty box victories. In 20 out of 37 regions, the combined number of empty box votes and abstention exceeded the votes obtained by the sole candidate pair, while Bangka Regency and Pangkalpinang City recorded empty box victories. This study shows that single candidate elections are better understood as arenas in which legitimacy is politically negotiated through the expressed consent reflected in support, rejection, and abstention.